1982
DOI: 10.1095/biolreprod26.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Actin in Human Spermatozoa

Abstract: An actin-like material was extracted from human spermatozoa. The material comigrated with actin on sodium dodecylsulfate (SDS) polyacrylamide gel electrophoresis, and showed specific affinity for myosin. Purified anti-actin antibodies were used to localize actin to the posterior region of the sperm head and to the connecting piece, midpiece and mainpiece of the tail. Determination of the function of sperm actin requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…The antigen-antibody reaction was assessed by the secondary antibody tagged to 10 nm gold particles and the reaction complex was fixed with osmium tetroxide thereby achieving a dual effect of contrast enhancement. The consistency of the method despite the use of weak fixative cocktail is apparent from the results on actin localization and the antigenic distribution seen here which are very similar to those seen by others using immunofluorescence (Clarke et al, 1982;Flaherty et al, 1988;Virtanen et al, 1984;Vogl, 1989). Indirect immunogold studies on sperm sections from boar (Casale et al, 1988) and guinea pig (Herná ndezGonzá lez et al, 2000) have identified presence of actin in the acrosomal region.…”
Section: Immunogold Localization Of B-tubulinsupporting
confidence: 86%
“…The antigen-antibody reaction was assessed by the secondary antibody tagged to 10 nm gold particles and the reaction complex was fixed with osmium tetroxide thereby achieving a dual effect of contrast enhancement. The consistency of the method despite the use of weak fixative cocktail is apparent from the results on actin localization and the antigenic distribution seen here which are very similar to those seen by others using immunofluorescence (Clarke et al, 1982;Flaherty et al, 1988;Virtanen et al, 1984;Vogl, 1989). Indirect immunogold studies on sperm sections from boar (Casale et al, 1988) and guinea pig (Herná ndezGonzá lez et al, 2000) have identified presence of actin in the acrosomal region.…”
Section: Immunogold Localization Of B-tubulinsupporting
confidence: 86%
“…In mammalian sperm, the perforatorium, exposed once the acrosome reaction has released the hydrolytic contents of the acrosomal cap and collar, acts as a mechanical tool with which the spermatozoan cuts through the zona pellucida of the egg (35). Actin in mammalian sperm may play a role in membrane fusions leading to the acrosome reaction and sperm-egg fusion since actin is present in the sperm tail, connecting piece, and posterior region of the sperm head in human and hamster sperm (6,31) and in the postacrosomal region of sperm from eight mammalian species, including mice (7; J. E. Welch and M. G. O'Rand, Dev. Biol., in press).…”
Section: Discussionmentioning
confidence: 99%
“…A rigid postacrosomal sheath is a putative site for actin in a number of mammalian spermatozoa (Clarke and Yanagimachi, 1978;Tamblyn, 1980;Clarke et al, 1982;Flaherty et al, 1986Flaherty et al, , 1988Yagi and Paranko, 1992), where it may interact with actin-binding proteins such as spectrin (Kann et al, 1993) and a group of basic proteins including calicin and multiple band proteins (Longo et al, 1987;Paranko et al, 19881, and with less well identified silver binding proteins (Yagi and Paranko, 1994).…”
Section: Lmmunolocalization Ofmentioning
confidence: 99%